(untitled) (E Conference Zone, 2022)
A brief analysis of a work by a conductor serves as a factor for the orchestra to enter the work environment. Explaining the essence of a work in terms of phrases by the conductor helps to analyze the work artistically. This article discusses the factors of a broader understanding of the content of the work during the performance of the work through artistic analysis of the work.